Quantifying worldwide economic distress - Delbianco, Fernando Andrés (2019)
This paper proposes a new measure for worldwide economic distress, which can bedescribed as the proportion of the gross domestic product (GDP) affected by countrylevel financial crises. It proves that this measure has the desirable properties of fair and representative indices. It also adequately justifies the beliefs of some economists that financial crises have negative effects on economicperformance.